Intestinal absorbability of three Radix Puerariae isoflavones including daidzein, daidzin and puerarin - Zhang Li; Pan Siu Antony; Lin Ge; Zuo Zhong (BMC, 2011)
Abstract Background Radix Puerariae (Gegen) contains abundant isoflavones in the forms of glycosides and aglycones, such as daidzein, daidzin and puerarin. This study aims to investigate the intestinal absorbability and mechanism of these three structurally related isoflavones. Methods The bi-directional transport of these three isoflavones in Caco-2 monolayer model was performed to evaluate their absorbability and involvement of transporters in Transwell. In vitro incubation of daidzin and puerarin with rat intestinal microvilli preparation was conducted to estimate their potential form of absorption in vivo. Results Daidzein demonstrated passive diffusion transport while puerarin did not. Daidzin showed basolateral-to-apical transport and the absorption extent could be reduced by 50% in the presence of MK571, a multidrug resistance-associated protein inhibitor (MRP). The in vitro incubation study of daidzin and puerarin indicated that daidzin was hydrolyzed to daidzein whereas puerarin remained unchanged. Conclusion While daidzein was transported more efficiently, puerarin was resistant to intestinal hydrolysis and inefficiently transported across intestinal epithelium. Daidzin demonstrated a low intestinal absorbability due to a significant efflux transport mediated by MRPs. Daidzin was likely to be hydrolyzed by intestinal microvilli and subsequently released daidzein for intestinal absorption.